2019
DOI: 10.1016/j.algal.2019.101576
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal variation in nitrogen, amino acid, protein and nitrogen-to-protein conversion factors of commercially cultivated Faroese Saccharina latissima

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
6
19
0
Order By: Relevance
“…Specific nitrogen-to-protein conversion factors (K p ) based on total amino acids are needed for S. latissima, because the commonly used conversion factor of 6.25 previously used for seaweed tends to overestimate the protein content (Lourenço et al 2002;Maehre et al 2018), thereby misleading consumers. The overall K p average across locations, depths and seasons of 3.8 ± 0.1 found in this study lies within the range of earlier published values of 2.0 and 6.25 (Schiener et al 2015;Angell et al 2016;Nielsen et al 2016;Biancarosa et al 2017;Manns et al 2017;Sharma et al 2018;Bak et al 2019). K p was only significantly higher at 1-2 m than at 8-9 m depths when kelp was affected by freshwater runoff, suggesting that it is acceptable to use the same K p value of 3.8 for S. latissima cultivated at different depths in full marine salinity conditions.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Specific nitrogen-to-protein conversion factors (K p ) based on total amino acids are needed for S. latissima, because the commonly used conversion factor of 6.25 previously used for seaweed tends to overestimate the protein content (Lourenço et al 2002;Maehre et al 2018), thereby misleading consumers. The overall K p average across locations, depths and seasons of 3.8 ± 0.1 found in this study lies within the range of earlier published values of 2.0 and 6.25 (Schiener et al 2015;Angell et al 2016;Nielsen et al 2016;Biancarosa et al 2017;Manns et al 2017;Sharma et al 2018;Bak et al 2019). K p was only significantly higher at 1-2 m than at 8-9 m depths when kelp was affected by freshwater runoff, suggesting that it is acceptable to use the same K p value of 3.8 for S. latissima cultivated at different depths in full marine salinity conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Manns et al (2017) found a decrease in Q N in May-July and suggested that the Q N was a more reliable indicator of the physiological nutritional state of the seaweeds than the ambient nitrate concentration. Even though the ash content of the seaweed followed the same seasonal pattern as Q N , the variation in nitrogen content has not been found to be related to the content of ash (Bak et al 2019). The ash content has, however, been found to be negatively correlated with frond length (Nielsen et al 2016), which agrees largely with our results.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations